2020
DOI: 10.1088/1757-899x/722/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health and Safety Effects on Productivity in a Garment Factory Using Structural Equation Modeling

Abstract: An industry goal is to create a product to make a profit. Development of human resources is one important thing for a company to consider. Companies have an opportunity to increase work productivity by the rules of OHS (Occupational Health and Safety). This study aimed to: (1) Partially determine the influence of work safety on employee productivity. (2) Partially determine the influence of health on employee productivity. (3) Simultaneously determine the influence of health and safety on employee productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[ 4 , 5 , 26 ] noted that safety practices have an impact on performance whilst the authors in Ref. [ 27 ] indicated that safety intervention has no impact on productivity performance. In addition, authors in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 , 5 , 26 ] noted that safety practices have an impact on performance whilst the authors in Ref. [ 27 ] indicated that safety intervention has no impact on productivity performance. In addition, authors in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was randomly distributed [ 6 , 26 ] to service companies in Zimbabwe that are registered with the Zimbabwe National Chamber of Commerce (ZNCC). Random sampling was used because, in SEM, high sample sizes are required [ 27 ]. Also, it gives participants equal opportunities to be selected [ 5 ].…”
Section: Methodsmentioning
confidence: 99%